Cigarette Smoke Induced Airway Inflammation Is Independent of NF-κB Signalling - Rastrick, Joseph M. D.; Stevenson, Christopher S.; Eltom, Suffwan; Grace, Megan; Davies, Meirion; Kilty, Iain; Evans, Steven M.; Pasparakis, Manolis; Catley, Matthew C.; Lawrence, Toby; Adcock, Ian M.; Belvisi, Maria G.; et al. (PLOS ONE, 2013)
Rationale COPD is an inflammatory lung disease largely associated with exposure to cigarette smoke (CS). The mechanism by which CS leads to the pathogenesis of COPD is currently unclear; it is known however that many of the inflammatory mediators present in the COPD lung can be produced via the actions of the transcription factor Nuclear Factor-kappaB (NF-κB) and its upstream signalling kinase, Inhibitor of κB kinase-2 (IKK-2). Therefore the NF-κB/IKK-2 signalling pathway may represent a therapeutic target to attenuate the inflammation associated with COPD. Aim To use a range of assays, genetically modified animals and pharmacological tools to determine the role of NF-κB in CS-induced airway inflammation. Methods NF-κB pathway activation was measured in pre-clinical models of CS-induced airway inflammation and in human lung tissue from COPD patients. This data was complemented by employing mice missing a functional NF-κB pathway in specific cell types (epithelial and myeloid cells) and with systemic inhibitors of IKK-2. Results We showed in an airway inflammation model known to be NF-κB-dependent that the NF-κB pathway activity assays and modulators were functional in the mouse lung. Then, using the same methods, we demonstrated that the NF-κB pathway appears not to play an important role in the inflammation observed after exposure to CS. Furthermore, assaying human lung tissue revealed that in the clinical samples there was also no increase in NF-κB pathway activation in the COPD lung, suggesting that our pre-clinical data is translational to human disease. Conclusions In this study we present compelling evidence that the IKK-2/NF-κB signalling pathway does not play a prominent role in the inflammatory response to CS exposure and that this pathway may not be important in COPD pathogenesis.